Formal structure in sculptures (Ahmed Al Bahrani _ Alessandro Calo) (A comparative study ) - Miaad Mahdi Lafta ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The current research is concerned with studying (The Formal Combination in the Sculptures of Ahmed Al-Bahrani & Alessandro Calo) and discovering the assembly and synthetic technical skills of their sculptures. Hence, The first chapter included the methodological framework of the research, the research problem that formulated the hypothesis according to the following question (What is the formal combination in the sculptures of (Ahmed Al-Bahrani & Alessandro Calo)? Then, the importance of the research and the need for it, the research objective, the limits of the research, and the definition of terminology, while the theoretical framework included, first: (the concept of philosophical and artistic combination), second: (formal combination in modern and contemporary arts). As for the research procedures, it included, first: the method used in the research, as the researcher relied on the analytical descriptive approach, then the researcher identified the research community with (60) sculptural works for both sculptors, then the research sample was determined, which was represented by (6) models chosen intentionally, then the researcher reviewed the results and conclusions.